Digital Storytelling as an Innovative Approach to Developing Narrative Writing Skills in Indonesian EFL Contexts - Sayyida Natsa Natsa; Siswoyo Siswoyo (Universitas Muhammadiyah Lampung, 2024)
This study investigated the effectiveness of digital storytelling in enhancing senior high school students narrative writing skills. A quantitative quasi-experimental design was employed involving 60 tenth-grade students, who were divided into an experimental group (n = 30) and a control group (n = 30). Data were collected through narrative writing tests administered as pretests and posttests and analyzed using descriptive statistics, paired sample t-tests, and independent sample t-tests. The results showed that the experimental groups mean score increased significantly from 64.06 on the pretest to 81.39 on the posttest, while the control group improved from 64.06 to 71.90. The paired sample t-test revealed a significant improvement in the experimental group (p < 0.05), and the independent sample t-test indicated a significant difference between the posttest scores of both groups (p < 0.05). These findings demonstrate that digital storytelling is more effective than conventional instruction in improving students narrative writing ability. However, this study was limited to a single school and a relatively short intervention period, which may restrict the generalizability of the findings. Therefore, it is recommended that educators integrate digital storytelling into writing instruction to promote creativity, engagement, and digital literacy, while future research should involve broader samples and longer implementation periods.